Scaling theory and computer simulation of star polymers in good solvents - Ohno, K. (Condensed Matter Physics, 2002)
The scaling theories and the results of the renormalization-group ε = 4−d expansion ( d is the spatial dimensionality) as well as the computer simulations such as Monte Carlo simulations are extensively reviewed for star polymers with very long flexible arms of equal length in a dilute solution of the good solvent limit, with a close connection to general polymer networks. In particular, the asymptotic behaviour of the conformational and entropic quantities in the long chain limit is discussed in detail in terms of the polymer-magnetism analogy. Discussions are given not only for static properties such as the distribution functions and the osmotic pressure or entropy but also for dynamic properties such as the relaxation time and the intrinsic viscosity of star polymers.